2019
DOI: 10.1186/s12909-019-1636-5
|View full text |Cite
|
Sign up to set email alerts
|

Promoting medical competencies through a didactic tutor qualification programme – a qualitative study based on the CanMEDS Physician Competency Framework

Abstract: Background In peer-led tutorial courses, qualified medical students (“tutors”) provide their peers with opportunities to deepen their theoretical knowledge effectively and to practice clinical skills already in preclinical semesters. At the Medical Faculty of Heidelberg University, a structured medical didactic qualification programme prepares and trains future tutors for their responsibilities. This programme consists of four modules: 1. medical didactics and group leadership, 2. subject-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Alvarez [ 23 ] interviewed anatomy peer teachers to explore which competencies they had developed. Homberg [ 24 ] analyzed which competencies were present in the didactic qualification program for peer skills teachers using input from peer teachers and training coordinators. Both studies used the CanMEDS framework and concluded that all roles, with exception for health advocate, were present.…”
Section: Discussionmentioning
confidence: 99%
“…Alvarez [ 23 ] interviewed anatomy peer teachers to explore which competencies they had developed. Homberg [ 24 ] analyzed which competencies were present in the didactic qualification program for peer skills teachers using input from peer teachers and training coordinators. Both studies used the CanMEDS framework and concluded that all roles, with exception for health advocate, were present.…”
Section: Discussionmentioning
confidence: 99%
“…Providing feedback to peers is seen as an effective learning experience for students [33]. In regard to the CanMEDS competencies, peer tutoring enhances the role of the scholar [34,35]. Interestingly, the concepts of peer teaching and peer assessing have not yet been shown to be effective or increase teaching skills.…”
Section: Peer Assessors Can Improve Their Clinical Social and Teachimentioning
confidence: 99%
“…At the beginning of the learning methods of FDAP, lecturer should explain the purpose of learning, build a positive attitude toward the subject, and describe something that is expected by the students [36]. Lecturers must first explain the processes and procedures in detail in order to better understand this method and [37]. The tutors must teach the students that the main objective of students to search and learn a large amount of information is to investigate critical issues related to the case.…”
Section: Discussionmentioning
confidence: 99%